The Raman Spectrum of the CH(3)NH(3)Pbl(3) Hybrid Perovskite: Interplay of Theory and Experiment - Quarti, C; Grancini, G; Mosconi, E; Bruno, P; Ball, J; Lee, M; Snaith, H; Petrozza, A; De Angelis, F (2014)
We report the low-frequency resonant Raman spectrum of methylammonium lead-iodide, a prototypical perovskite for solar cells applications, on mesoporous Al2O3. The measured spectrum assignment is assisted by DFT simulations of the Raman spectra of suitable periodic and model systems. The bands at 62 and 94 cm-1 are assigned respectively to the bending and to the stretching of the Pb-I bonds, and are thus diagnostic modes of the inorganic cage. We also assign the librations of the organic cations at 119 and 154 cm-1. The broad, unstructured 200-400 cm-1 features are assigned to the torsional mode of the methylammonium cations, which we propose as a marker of the orientational disorder of the material. Our study provides the basis to interpret the Raman spectra of organohalide perovskites, which may allow one to further understand the properties of this important class of materials in relation to their full exploitation in solar cells. © 2013 American Chemical Society.